Electrical imaging of the northern part of Lakshdweep Islands - Subbarao, P.B.V.; Singh, A.K. (My University, 2010)
Magnetovariational fields recorded by an array of magnetometers in five different Lakshdweep Islands were analysed to infer the subsurface structure of the region. Only nighttime magnetovariational fields were used because of the prevailing uniform source field conditions. Transfer functions showing the relationship between vertical and horizontal magnetic field components were computed for a period range of 8–128 min using robust regression analysis. Obsrved induction pattern at all stations is dominated by island effect. Two-dimensional modelling across the northern part of the Chagos–Laccadive Ridge (CLR) brings out midcrustal conductivity anomaly associated with magmatic intrusions/fluids along the track of Reunion hotspot. This anomaly could be delineated after eliminating the shielding effect due to seawater column using 3-D thin sheet approximation. Conductivity anomaly may be associated with massive intrusions due to hotspot volcanism, during the northward drift of Indian plate over the Reunion mantle plume.
Keywords: Conductivity anomaly; Lakshdweep Islands; Magnetovariational studies; Reunion hotspot